Dedolomitization Potential of Fluids from Gypsum-to-Anhydrite Conversion: Mass Balance Constraints from the Late Permian Zechstein-2-Carbonates in NW Germany - M. Hallenberger; L. Reuning; J. Schoenherr (Geofluids)
The Zechstein-2-Carbonates represent one of the most prolific hydrocarbon systems of Central Europe. Carbonate reservoir quality is primarily controlled by mineralogy, with dolomite representing moderate-to-good porosities and calcite commonly representing low porosities. Current models suggest that this calcite is the result of a basin-wide phase of dedolomitization. The calcium (Ca) source for the dedolomites is thought to be derived from the fluids liberated during gypsum-to-anhydrite conversion. We present an easy-to-use and generally applicable template to estimate the dedolomitization potential of these fluids. Depending on reaction stoichiometry, salinity, and temperature, we estimate that between 2.8⁎10−3 m3 and 6.2⁎10−3 m3 of calcite may replace dolomite for each m3 of anhydrite created. Within the constraints dictated by the environment of the late Permian Zechstein basin, we estimate that about 5⁎10−3 m3 of dedolomite is created for each m3 of anhydrite. Mass balance constraints indicate that fluids derived from gypsum-to-anhydrite conversion account for less than 1% of the observed dedolomite in most of the studied industry wells from northern Germany.